2015
DOI: 10.1158/1940-6207.capr-15-0126
|View full text |Cite
|
Sign up to set email alerts
|

NSAID Use and Risk of Hepatocellular Carcinoma and Intrahepatic Cholangiocarcinoma: The Liver Cancer Pooling Project

Abstract: Chronic inflammation plays a pivotal role in the pathogenesis of hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC), the two most common types of liver cancer. A number of prior experimental studies have suggested that non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin and ibuprofen, may potentially protect against liver cancer. However, no observational study has examined the association between aspirin duration and dose or other over-the-counter non-aspirin NSAIDs, such a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
102
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 41 publications
6
102
1
1
Order By: Relevance
“…Previous US-based large cohort studies suggested that NSAID use, specifically aspirin, was associated with lower risk of hepatocellular carcinoma (HCC) [9, 10]. In contrast, our study suggests a lack of association between NSAID use and liver cancer risk in the CPRD.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Previous US-based large cohort studies suggested that NSAID use, specifically aspirin, was associated with lower risk of hepatocellular carcinoma (HCC) [9, 10]. In contrast, our study suggests a lack of association between NSAID use and liver cancer risk in the CPRD.…”
Section: Discussioncontrasting
confidence: 88%
“…Experimental studies have shown that NSAIDs may inhibit liver cancer cellular growth and induce cell apoptosis by modifying cyclooxygenase (COX) enzymatic pathways which mediate inflammation [7, 8]. Two reports from large observational studies suggested that NSAID use, specifically aspirin, was associated with reduced risk of liver cancer [9, 10], but NSAID use was self-reported in these studies. Associations between prescription NSAID use and liver cancer have not been previously described.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective evidence specifically addressing aspirin dose and duration is limited to 2 previous cohort studies that assessed aspirin use at only 1 point in time. 9,10 As individual patterns of medication use may change over time, prospectively updated medication data are important for accurately estimating risk, particularly in diseases with prolonged latency. 11,12 Moreover, it remains controversial whether nonaspirin nonsteroidal anti-inflammatory drugs (NSAIDs), which share several mechanisms of action with aspirin, exert similar anti-HCC effects.…”
mentioning
confidence: 99%
“…Another retrospective study demonstrates that treatment of patients with chronic hepatitis B with aspirin and/or another antiplatelet agent clopidogrel (a P2Y12 ADP receptor antagonist) reduces the risk of HCC . Moreover, a pooled analysis of data from prospective cohort studies reveals that aspirin use inversely correlates with HCC risk, while the NSAID ibuprofen does not reduce HCC risk . In a chronic HBV‐induced HCC model, combination of aspirin and clopidogrel successfully prevents or delays hepatocarcinogenesis in mice .…”
Section: Epidemiological Evidence For the Prevention Of Cancer By Aspmentioning
confidence: 99%